2018
DOI: 10.1038/s41467-018-03082-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting genetic variation to uncover rules of transcription factor binding and chromatin accessibility

Abstract: Single-nucleotide variants that underlie phenotypic variation can affect chromatin occupancy of transcription factors (TFs). To delineate determinants of in vivo TF binding and chromatin accessibility, we introduce an approach that compares ChIP-seq and DNase-seq data sets from genetically divergent murine erythroid cell lines. The impact of discriminatory single-nucleotide variants on TF ChIP signal enables definition at single base resolution of in vivo binding characteristics of nuclear factors GATA1, TAL1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 82 publications
4
26
0
Order By: Relevance
“…However, interestingly, we observed some strong longrange interactions between motifs as far as 70 bp apart (Fig. 3B), an observation corroborated by a recent analysis of SNP effects on TAL1 ChIP-seq signal in erythroid cells that found that GATA1 motif mutations impact TAL1 binding at distances as great as 75 bp 13 . The interactions were also symmetric, such that mutating TAL1 demonstrated a distribution of on GATA1 (SFig.…”
Section: Comparison Of Dfim To Shap Interaction Scores and Pairwise Isupporting
confidence: 89%
“…However, interestingly, we observed some strong longrange interactions between motifs as far as 70 bp apart (Fig. 3B), an observation corroborated by a recent analysis of SNP effects on TAL1 ChIP-seq signal in erythroid cells that found that GATA1 motif mutations impact TAL1 binding at distances as great as 75 bp 13 . The interactions were also symmetric, such that mutating TAL1 demonstrated a distribution of on GATA1 (SFig.…”
Section: Comparison Of Dfim To Shap Interaction Scores and Pairwise Isupporting
confidence: 89%
“…This complex binds to the regulatory regions (i.e., active H3K27ac + enhancers) of genes involved in HSPC biology . In HSPCs, GATA2 marks a subset of bivalent H3K27me3 + H3K4me3 + regulatory regions that are bound by GATA1 upon erythroid differentiation and tend to be located close to erythroid‐specific genes—suggesting that GATA2 is at least partially involved in lineage priming . Lastly, upon activation of the BMP and Wnt signaling pathways in HSPCs, SMAD and TCF co‐occupy GATA2‐bound enhancers associated with actively transcribed genes and enhance transcriptional activation by GATA2 …”
Section: Gata2mentioning
confidence: 99%
“…24,25,37,38 However, GATA1 and KLF1 were shown to bind conjointly to several erythroid enhancers and genes and thus cooperate in the gene induction process. 15,24,25,32,[39][40][41] The transcriptional repressor GFI1B and GATA1 co-bind to some gene loci that are repressed upon erythroid development-suggesting that the two factors cooperate to repress gene expression in erythroid cells. 9,27 The transcriptional co-factor FOG1 is required for GATA1 activating or repressing activity at many loci in erythroid and megakaryocytic cells, [33][34][35]42 although genomewide studies of FOG1 occupancy have not yet been performed.…”
Section: Gata1mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some CTCF loops are not constitutive, but rather cell type‐specific. This “dynamic” subset might involve several and non‐mutually exclusive mechanisms, such as: (i) tissue‐specific binding of CTCF mediated by cell type‐specific epigenetic modifications or transcription factors (Wang et al , ; Behera et al , ) and (ii) constitutively bound CTCF sites engaging into tissue‐specific interactions due to the action of additional “looping” co‐factors (Phillips‐Cremins et al , ; Huang et al , ).…”
Section: Introductionmentioning
confidence: 99%